Design and Build a Robot for Fertilizer Irrigation in Agricultural Land Using IoT - Raihan Habib Rahadi; Husnul Khair; Milli Alfhi Syari, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This research presents the design and development of an IoT-based fertilizing robot to improve efficiency and effectiveness in fertilizing chili crops. The system utilizes the ESP32 microcontroller, TCRT5000 sensor as a line follower, L298N motor driver, ultrasonic sensor for fertilizer tank level detection, and a DC pump for spraying. Control and monitoring are carried out through the Blynk application connected via Wi-Fi, allowing users to operate the robot and receive real-time notifications when the fertilizer tank is nearly empty. The test results show that the robot can follow the designated path, stop at specific points, and spray fertilizer automatically with a functionality success rate of more than 90%.